Development of information structure in acquisition of German as an early foreign language - Sopata, Aldona (Glottodidactica, 2018)
The article investigates the use of pronouns to express subjects and objects in early acquisition of German as a foreign language. The main goal of the investigation is to shed some light on the process of development of information structure in the minds of young learners of a foreign language. The study investigates longitudinal data from children who were exposed to German in a school setting from the age of 7 or 9. The results of the empirical study show that children acquiring German in a school setting use a relatively high number of pronouns for subjects, but they rarely use pronouns to express objects. The pedagogical implication for developing an optimal outline for foreign language teaching in early childhood is the necessity to pay more attention to the development of pragmatic and discourse skills of children learning a foreign language.